THE IMPORTANCE OF WELL-ADJUSTED PUBLIC REGULATION AND THE IMPACT OF DEFICIENCIES ON THE FUNCTIONING OF THE STATE IN CRISIS SITUATIONS – THE EXAMPLE OF THE CZECH REPUBLIC IN THE EUROPEAN CONSTITUTIONAL CONTEXT - Jan Kudrna (International Comparative Jurisprudence, 2023)
This article is dedicated to the importance of well-adjusted public regulation and the impact of deficiencies on the functioning of the state in crisis situations, using the example of the Czech Republic. The present article focuses on those parts of the constitutional system of the Czech Republic (in comparison with other comparable countries) which regulate special procedures in ensuring the security of the state and the fulfilment of international obligations, for example in the field of common defence against attack. Some of the provisions analysed have not yet been applied, while others have and there is sufficient evidence from their daily application and practice. The first group of cases includes the procedure for declaring a state of war, which is a legal condition for the application of a number of measures necessary for the defence of the state and the support of treaty allies. The second group includes in particular the issue of sending the Czech Armed Forces abroad, which is closely related to the Czech Republic’s obligations towards NATO and its VJTF forces. The constitutional procedure for the approval of flights of foreign armed forces over the territory of the Czech Republic is not feasible in its current form. A legal comparison shows the importance of balanced constitutional and legal regulation on the one hand. On the other hand, the potential problems that, under the rule of law, inappropriate legal regulation can bring not only for the state itself, but also for its partners in the international community are highlighted. The article presents, through comparative legal methods, the notion that that although most European states with a parliamentary form of government are rather restrained players in the use of armed forces outside their territory, a significant proportion of them do give the executive the possibility to dispose of these armed forces. This can only occur if necessary, with subsequent parliamentary control, and not under the full control of the parliament through its consent given in advance.Possible proposals to address the problems described are also offered. The analysis shows that, in comparison with other states with similar sizes, power, history and needs, political representation in the Czech Republic is in a kind of mental trap. This could even complicate the fulfilment not only of the security interests of the state, but also of its obligations to its partners in the international community.